Special training of highway cyclists considering energy metabolism types - Bakayev, V.; Bolotin, A. (Scientific Journal of Sport and Performance, 2022)
The competitive activity of racers on the highway makes high demands on the level of their physical fitness, since the competition can be held in the form of a multi-day race. The training of road racers is based on the development of physical qualities, among which the most important for them are different types of endurance. The development of these qualities is possible only with a purposeful impact on their physiological systems and, in particular, on the mechanisms of energy supply of muscle activity.